RESPON IBU RUMAH TANGGA TERHADAP PROGRAM FLASH SALE TANGGAL KEMBAR DALAM MENDORONG KEPUTUSAN PEMBELIAN TIKTOK SHOP DI DESA CANGKRINGRANDU - Andini Dwi Kinanti; Regyta Yollanda; Daud Sipasulta; Naura Aurellia; Tan Evan Tandiyono (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of digital technology and e-commerce has brought significant changes to people's consumption patterns, including among housewives. Easy internet access and the presence of various online shopping platforms have made shopping activities more practical and efficient. One platform that is growing rapidly in Indonesia is TikTok Shop, an e-commerce feature that combines entertainment and shopping transactions in one application. TikTok Shop offers various promotional strategies such as flash sales, double date promotions, discount vouchers, free shipping, and live streaming features that can attract consumers' attention and encourage purchasing decisions in a short time. This study aims to analyze the response of housewives to the double date flash sale program in encouraging purchasing decisions at TikTok Shop in the community of Cangkringrandu Village, Jombang Regency. The research method used a qualitative approach with data collection techniques through in-depth interviews with five housewives who actively use TikTok Shop as an online shopping tool. The results show that the flash sale program and double date promotions have a significant influence on consumer purchasing decisions.